Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To solve the expression \( 2 \sin \left(2 \sin^{-1} x\right) \), we can utilize trigonometric identities and properties of inverse trigonometric functions. Here’s the step-by-step solution:
1. Understanding the Inner Function: Let’s first consider the inner function \( \sin^{-1}(x) \). Suppose \( \theta = \sin^{-1}(x) \), which implies \( \sin(\theta) = x \) and \( \theta \) is an angle.
2. Double Angle Identity: We now need to evaluate \( \sin(2\theta) \) where \( \theta = \sin^{-1}(x) \). Using the double angle identity for sine, we have:
[tex]\[ \sin(2\theta) = 2 \sin(\theta) \cos(\theta) \][/tex]
3. Substitution for \( \sin(\theta) \): From our initial substitution, we know \( \sin(\theta) = x \).
4. Finding \( \cos(\theta) \): To find \( \cos(\theta) \), we use the Pythagorean identity. Since \( \sin(\theta) = x \), we have:
[tex]\[ \cos(\theta) = \sqrt{1 - \sin^2(\theta)} = \sqrt{1 - x^2} \][/tex]
5. Putting it All Together: Using the information above in the double angle identity, we get:
[tex]\[ \sin(2\theta) = 2 \sin(\theta) \cos(\theta) = 2x \sqrt{1 - x^2} \][/tex]
6. Scaling by 2: Finally, the original expression was \( 2 \sin (2 \sin^{-1} x) \):
[tex]\[ 2 \sin(2 \theta) = 2(2 x \sqrt{1 - x^2}) = 4 x \sqrt{1 - x^2} \][/tex]
Therefore, the expression \( 2 \sin \left(2 \sin^{-1} x \right) \) can be written as the algebraic expression:
[tex]\[ 4 x \sqrt{1 - x^2} \][/tex]
1. Understanding the Inner Function: Let’s first consider the inner function \( \sin^{-1}(x) \). Suppose \( \theta = \sin^{-1}(x) \), which implies \( \sin(\theta) = x \) and \( \theta \) is an angle.
2. Double Angle Identity: We now need to evaluate \( \sin(2\theta) \) where \( \theta = \sin^{-1}(x) \). Using the double angle identity for sine, we have:
[tex]\[ \sin(2\theta) = 2 \sin(\theta) \cos(\theta) \][/tex]
3. Substitution for \( \sin(\theta) \): From our initial substitution, we know \( \sin(\theta) = x \).
4. Finding \( \cos(\theta) \): To find \( \cos(\theta) \), we use the Pythagorean identity. Since \( \sin(\theta) = x \), we have:
[tex]\[ \cos(\theta) = \sqrt{1 - \sin^2(\theta)} = \sqrt{1 - x^2} \][/tex]
5. Putting it All Together: Using the information above in the double angle identity, we get:
[tex]\[ \sin(2\theta) = 2 \sin(\theta) \cos(\theta) = 2x \sqrt{1 - x^2} \][/tex]
6. Scaling by 2: Finally, the original expression was \( 2 \sin (2 \sin^{-1} x) \):
[tex]\[ 2 \sin(2 \theta) = 2(2 x \sqrt{1 - x^2}) = 4 x \sqrt{1 - x^2} \][/tex]
Therefore, the expression \( 2 \sin \left(2 \sin^{-1} x \right) \) can be written as the algebraic expression:
[tex]\[ 4 x \sqrt{1 - x^2} \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.